Water Level and Solar Panel Power Monitoring System Based on the Internet of Things (IoT) - Affan Bachri; Abdur Rohman Wakhid; Muhammad Aflah Kafabi (Journal of Electrical Engineering and Computer (JEECOM), 2025)
Water storage management still requires direct supervision in many household and small-scale applications, while a remote monitoring system also needs a reliable energy supply. This study develops an integrated Internet of Things system that measures water level and photovoltaic electrical parameters in real time. The prototype uses an ESP32, a waterproof JSN-SR04T ultrasonic sensor, two INA219 modules, a 20 Wp solar panel, a PWM solar charge controller, a 12 V battery, ThingSpeak, and a Telegram Bot. Testing covered microcontroller connectivity, distance measurement accuracy, electrical sensing, solar panel output, battery operation, cloud data delivery, and integrated system performance. The JSN-SR04T produced an average reading of 10.16 cm for a 10.00 cm reference, with an average absolute deviation of 0.16 cm. INA219 voltage measurements showed a mean relative error of 2.91% against a multimeter. During integrated testing, the water level remained at 12.0-12.4 cm, solar panel voltage reached 13.44-13.45 V, and panel power reached 4.40-4.41 W. ThingSpeak displayed the measurements continuously, while Telegram delivered synchronized status information. These results show that the proposed system supports remote water-level and energy-source monitoring using an autonomous solar supply.